State and output feedback control for Lipschitz nonlinear systems in reciprocal state space: synthesis and real-time validation - Assem Thabet; Ghazi Bel Haj Frej; Noussaiba Gasmi; Karim Mansouri; Eric Chauveau (Institute of Advanced Engineering and Science, 2022)
In industrials process and many studies cases, state and output derivative variables can be easily modeled in reciprocal state space (RSS) form than the standard one. Formulation of stabilization problem with a guaranteed cost control using feedback principle for Lipschitz nonlinear systems (LNS) in RSS is presented in this brief. The asymptotic stability, using the proper Lyapunov functions of the closed-loop system, is guaranteed. The control design problem is guaranteed through a resolution of linear matrix inequalities (LMI) technique under certain lemmas and minimization of non-standard cost control. Experimental validation shows the good performances of the proposed method using real-time implementation (RTI) with a digital signal processing (DSP) device (Arduino MEGA 2560).